Impact of precarious work on neighborhood health: Concept mapping by a community/academic partnership. Issue 1 (15th October 2019) - Velonis, Alisa J.; Hebert‐Beirne, Jeni; Conroy, Lorraine M.; Hernandez, Marcella; Castaneda, Dolores; Forst, Linda
Abstract: Objective: As part of community‐based participatory research (CBPR) examining precarious employment and community health, academic, and community researchers used concept mapping to explore how residents in two high hardship neighborhoods perceive the impact of work on health. Methods: Between January and May 2017, 292 individuals who lived or worked in two contiguous Chicago neighborhoods were engaged in brainstorming, sorting, and rating activities. Multidimensional scaling and hierarchical cluster analysis were applied, and findings were interpreted by a community‐academic partnership. Results: Brainstorming resulted in 55 unique ways that work impacts health, each of which was rated on its perceived impact on health and prevalence in the neighborhood. Four major themes emerged: Healthy Aspects of Work, Systemic/Structural Injustices, Lack of Control/Exploitation, and Psychological/Physical Stress, which was a multidimensional, cross‐cutting theme. Conclusion: These findings provide critical insight into community perceptions of the mechanisms by which work influences health, providing a basis for community‐driven, sustainable, work‐focused interventions that promote community health.